Factors that affect employees' satisfaction toward performance appraisal system under Malaysian remuneration system: a case in immigration department Malaysia Kuching, Sarawak - Ch'ng, Eng Hiong (Universiti Malaysia Sarawak (UNIMAS), 2010)
This study is to detennine factors affecting Employees' Satisfaction toward New Perfonnance Appraisal System (NPAS) under the Malaysian Remuneration System (MRS) in Immigration Department Malaysia Kuching Sarawak. The targeted group is Immigration Officers (Grade KP38 to KP17) in Kuching-Samarahan Division, Sarawak. The aim of this research in Immigration Department Malaysia Sarawak is its importance in the development of the State development and economy especially with the creation of Sarawak Corridor of Renewable Energy (SCORE)) One of the Five-Prong Development Strategy for the SCORE is to accelerate human capital development within the Corridor with new learning centers and controlled immigration of skilled foreign workers. Moreover, the department is responsible in facilitating the government's effort in promoting tourism industry that can contribute income for the State. Findings were made based on the data collected from 151 employees that comprised of Supporting Group from Grade KP38 to KP17 under Malaysian Remuneration System (MRS) with the aid of questionnaires. The result of the findings showed that Immigration Officers are slightly satisfied with the New Perfonnance Appraisal System (NPAS) under the Malaysian Remuneration System (MRS). The analysis by using t-Test, Pearson correlation and ANOVA showed that factors affecting Employees' Satisfaction toward New Perfonnance Appraisal System (NPAS) under the Malaysian Remuneration System (MRS) in Immigration Department Malaysia Kuching Sarawak were positively correlated with Age, Annual Work Target, career development Aspects, promotion, salary & benefits and training & development. For future research, some recommendations made in this study can be further explored this particular area of study. The data collected was analyzed using the "Statistical Packages for Social science" (SPSS) version 17.0